Optimasi Efisiensi Perawatan Air Conditioning Tipe Split dengan Penerapan Pembersih Filter Otomatis Berbasis Condition-Base Maintenance - Hartman, Bemly; Mustofa Kamal, Dianta; Zainuri, Fuad (P3M Politeknik Negeri Cilacap, 2025)
The increasing use of split air conditioners (AC) in various sectors demands efficient maintenance solutions to ensure optimal performance and improve energy efficiency. Time-based maintenance (TBM), the commonly used method, often leads to premature or delayed maintenance, reducing system efficiency and increasing operational costs. Previous studies have not fully explored the application of condition-based maintenance (CBM) for AC filter maintenance, especially in developing automated systems. A significant research gap exists due to the lack of real-time solutions for accurately detecting filter conditions and enabling maintenance without manual intervention. This study aims to develop an automated AC filter cleaner prototype based on CBM by integrating sensors, microcontrollers, and actuators. The results show the system reduces energy consumption by up to 58%, shortens cleaning time by 75%, and eliminates water use. In conclusion, the proposed prototype offers an innovative and efficient solution for enhancing operational performance and reducing costs.